Impact of genotyping (PTPN2, rs2542151) and (MBOAT7, rs641738) in prediction of fibrosis in Metabolic dysfunction- associated steatotic liver disease’ patients - Abdelsattar, Shimaa; Al-Amodi, Hiba S.; Kamel, Hala F. M.; Kasemy, Zeinab A.; Darwish, Ehab; Mosbeh, Asmaa; Sakr, Ayman A.; Elgazzar, Hanaa M.; Abdelkareem, Mervat; Abozeid, Mai; Zewain, Shimaa K.; Bedair, Hanan M.; et al. (Frontiers in Endocrinology, 2025)
IntroductionNumerous risk loci have been identified to have an essential role in Metabolic associated steatotic liver disease (MASLD) susceptibility and progression. The role of membrane-bound O-acyltransferase domain containing 7 (MBOAT7, rs641738) and protein tyrosine phosphatase non-receptor type 2 (PTPN2, rs2542151) genes in the risk of significant fibrosis in MASLD patients is still unclear. The aim of this study was to examine the association between MBOAT7 rs641738 and PTPN2 rs2542151 genotypes and the risk of significant fibrosis in Egyptian individuals with MASLD.MethodsWe enrolled 142 patients with varying degrees of MASLD and 142 healthy controls with no evidence of MASLD. All subjects underwent biochemical tests and genotyping of PTPN2 rs2542151 and MBOAT7 rs641738 by real-time PCR. Additionally, patients were divided according to fibrosis stages assessed by transient elastography (Fibroscan) into 103 patients with early fibrosis (F0, F1) and 39 with significant fibrosis (≥ F2).Results and discussionThe study revealed that T allele and T/T genotype of MBOAT7 rs641738 were more frequent among MASLD patients compared to controls, with higher frequency in the significant fibrosis subgroup compared to early fibrosis or control groups. Regarding PTPN2 rs2542151, the G allele and G/G genotype were more frequent among MASLD patients compared to controls and showed higher frequency among the significant fibrosis group than controls. Multivariable regression analysis revealed that triglycerides, hepatic steatosis index, MBOAT7 rs641738 (C/T+T/T), and PTPN2 rs2542151 (G/T+G/G) were independent predictors of MASLD susceptibility. Only PTPN2 rs2542151 (G/T+G/G) was the independent predictor of significant fibrosis in MASLD patients. In conclusion, PTPN2 rs2542151 and MBOAT7 rs641738 SNPs are associated with MASLD susceptibility, while only PTPN2 rs2542151 mutations are associated with fibrosis progression.